Effect of the pig rearing system on the final volatile profile of Iberian dry-cured ham as detected by PTR-ToF-MS - Sanchez del Pulgar, J. (2013)
The volatile compound profile of dry-cured Iberian ham lean and subcutaneous fat from pigs fattened outdoors on acorn and pasture (Montanera) or on high-oleic concentrated feed (Campo) was investigated by proton transfer reaction time-of-flight mass spectrometry. In addition to the usual proton transfer ionization we implemented the novel switchable reagent ions system which allows the use of different precursor ions (H3O+, NO+ and O2+). The analysis of the lean and subcutaneous fat volatile compounds allowed good sample discrimination according to the diet. Differences were evident for several classes of compounds: in particular, Montanera hams showed higher concentrations of aldehydes and ketones and lower concentrations of sulfur-containing compounds compared to Campo hams. The use of NO+ as precursor ion confirmed the results obtained with H3O+ in terms of classification capability and provides additional analytical insights.